ANALYSIS OF POTATO SUPPLY CHAIN MANAGEMENT IN NGABLAK AND PAKIS DISTRICTS, MAGELANG REGENCY - Sembiring Depari, Muhammad Mukhlis; Roessali, Wiludjeng; Kusmiyati, Florentina (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The fluctuating price of potatoes every year as well as the high costs of distribution, storage, and maintenance mean that farmers earn less profit than expected. The research aims to analyze supply chain management, marketing efficiency, and potato supply chain risks. The research was carried out in September 2023 in Pakis and Ngablak Districts, Magelang Regency. This research uses a survey method with a descriptive approach. Determining the institutional sample uses snowball sampling while the farmer sample uses Cluster Sampling or Multistage Random Sampling method. The pattern of flow of information, finances, and goods runs smoothly. In the calculation of the farmer's share of large-grade potato commodities obtained at the research location, channel I was 84.61%, channel II was 85.71% and channel III was 80.00%, including in the efficient category. The farmer's share grade value was obtained by channel I at 75.00%, channel II at 77.77%, including in the efficient category, channel III at 70%, including in the inefficient category. The small farmer's share grade value obtained by channel I was 71.42%, channel II was 75%, which was included in the efficient category and channel III was 66.66%, which was not included in the efficient category. There are 23 risk agents and 15 risk events in the potato supply chain in Ngablak and Pakis Districts, Magelang Regency. Phase 1 HoR analysis provides results based on the Pareto diagram that there are 3 priority risk agents, namely crop failure, potatoes damaged in transit, and natural factors or disasters.